Patterns of abundance across geographical ranges as a predictor for responses to climate change: Evidence from UK rocky shores. Issue 10 (24th June 2020) - Vye, Siobhan R.; Dickens, Stephanie; Adams, Leoni; Bohn, Katrin; Chenery, Jade; Dobson, Nicola; Dunn, Ruth E.; Earp, Hannah S.; Evans, Megan; Foster, Charlotte; Grist, Hannah; Holt, Ben; et al.
Abstract: Aim: Understanding patterns in the abundance of species across thermal ranges can give useful insights into the potential impacts of climate change. The abundant‐centre hypothesis suggests that species will reach peak abundance at the centre of their thermal range where conditions are optimal, but evidence in support of this hypothesis is mixed and limited in geographical and taxonomic scope. We tested the applicability of the abundant‐centre hypothesis across a range of intertidal organisms using a large, citizen science‐generated data set. Location: UK. Methods: Species' abundance records were matched with their location within their thermal range. Patterns in abundance distribution for individual species, and across aggregated species abundances, were analysed using Kruskal–Wallis tests and quantile general additive models. Results: Individually, invertebrate species showed increasing abundances in the cooler half of the thermal range and decreasing abundances in the warmer half of the thermal range. The overall shape for aggregated invertebrate species abundances reflected a broad peak, with a cool‐skewed maximum abundance. Algal species showed little evidence for an abundant‐centre distribution individually, but overall the aggregated species abundances suggested a hump‐backed abundance distribution. Main Conclusions: Our study follows others in showing mixed support for the abundant‐centre hypothesis at an individual species level, but demonstrates an increased predictability in species responses when an aggregated overall response is considered.